Second homes: A bibliometric analysis and systematic literature review - Maria José Alonsopérez; Juan Gabriel Brida; Mara Leticia Rojas (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: Despite second homes having been extensively studied in the tourism area during the last two decades, there is a lack of updated review. This work presents a systematic literature review and a revision of the main issues studied. Methods: The document begins with a discussion about different concepts and definitions. It highlights the lack of an internationally accepted definition of second home tourism and proposed one. Then, our literature review in second homes shows the growth of publications, country specification, the affiliation of lead authors and the leading serial source titles. The review is based on a comprehensive search in Scopus through keywords. Additionally, the main topics and issues related to second homes are summarised. Results: Results show that the number of publications has grown almost steadily, with a maximum in 2018. American, Nordics and South African authors dominate second homes research. Publications have been shifted from Tourism Geographies journals to Tourism journals showing a greater specification in the area. Implications: Finally, based on our review on topics, we conclude that there is still more to study, most of all in the field of theoretical work, the analysis of economic, environmental, and social impacts and the role of unexpected events, such as Covid 19, that has changed the use of second homes.
Keywords: Z11; Z32; 330; Second homes tourism; Second homes impacts; Bibliometric Analysis